Growing-Service Systems: New Business Models for Modular Urban-Vertical Farming - Martin, Michael; Bustamante, Maria J. (Frontiers in Sustainable Food Systems, 2021)
To secure sustainable and resilient food systems, new approaches, innovations, techniques, and processes are needed. In recent years, urban farming firms have been developing and experimenting with innovative approaches to expand their offerings and connect with consumers in new ways. New business models are being developed to provide functions and services instead of traditional products to meet demands from consumers, retailers, and users. As such, modular growing systems are increasing in popularity to provide fresh produce, visual appeal, transparency, and other tailor-made functions and services in so-called ‘growing-service systems’ (GSS). Using GSS approaches, firms are developing and providing modular and small-scale farms in restaurants, residential spaces, supermarkets, and other commercial spaces, often including a large degree of automation and optimization of digital solutions to remotely control their operation. Using qualitative methods, the aim of this study is to explore and analyze the development of these novel GSS systems, highlighting different strategies, business models, motivations, and challenges. The results illustrate the divergence in approaches to GSSs for vertical farming. This includes different scales of modular units and varying business models for capturing value from the combination of products and services. All of the systems include varying degrees of automation and digitalized solutions to ensure the services are monitored, which is done to improve growing conditions and improve the experience for the users. Business-to-business systems are being developed as both market expansion and awareness-building strategies, where modular units are provided as a rental or subscription model that includes a number of services. Business-to-consumer systems are being introduced as an alternative for consumers, particularly in urban areas, to have greater control and access over growing their own fresh produce. The modules are purchased by consumers, which includes a number of ongoing services from the GSS firms. By categorizing and exploring these systems, this article offers novel insights and a first endeavor to distinguish these new GSS systems in the growing segment of urban agriculture, controlled-environment agriculture, and product-service system literature.